Sensitivity of clinical screening for detecting developmental dysplasia of the hip: a retrospective study - Enrica Pittaluga; Alexis Arnoux; Sophie Merckaert (Swiss Medical Weekly)
BACKGROUND: Detecting developmental dysplasia of the hip in infants is crucial. This study aimed to estimate the sensitivity of clinical screening for developmental dysplasia of the hip in a tertiary care setting. We compared clinical findings with ultrasound results to determine diagnostic accuracy.